Factors associated with red blood cell transfusions in very-low-birth-weight preterm infants in Brazilian neonatal units - Santos, Amelia Miyashiro Nunes dos; Guinsburg, Ruth; Almeida, Maria Fernanda Branco de; Procianoy, Renato Soibelman; Marba, Sergio Tadeu Martins; Ferri, Walusa Assad Gonçalves; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Lopes, José Maria Andrade; Moreira, Maria Elisabeth Lopes; Luz, Jorge Hecker; González, Maria Rafaela Conde; Meneses, Jucille do Amaral; et al. (BioMed Central LTD, 2015)
Preterm infants in neonatal intensive care units frequently receive red blood cells (RBC) transfusions due to the anemia of prematurity. A number of variables related to gestational age, severity of illness and transfusion practices adopted in the neonatal unit where the neonate was born may contribute to the prescription of RBC transfusions. This study aimed to analyse the frequency and factors associated with RBC transfusions in very-low-birth-weight preterm infants. A prospective cohort of 4283 preterm infants (gestational age: 29.9 ± 2.9 weeks; birth weight: 1084 ± 275 g) carried out at 16 university hospitals in Brazil between January 2009 and December 2011 was analysed. Factors associated with RBC transfusions were evaluated using univariate and multiple logistic regression analysis. A total of 2208 (51.6%) infants received RBC transfusions (variation per neonatal unit: 34.1% to 66.4%). RBC transfusions were significantly associated with gestational age (OR: -1.098; 95%CI: -1.12 to -1.04), SNAPPE II score (1.01; 1.00-1.02), apnea (1.69; 1.34-2.14), pulmonary hemorrhage (2.65; 1.74-4.031), need for oxygen at 28 days of life (1.56; 1.17-2.08), clinical sepsis (3.22; 2.55-4.05), necrotising enterocolitis (3.80; 2.26-6.41), grades III/IV intraventricular hemorrhage (1.64; 1.05-2.58), mechanical ventilation (2.27; 1.74-2.97), use of umbilical catheter (1.86; 1.35-2.57), parenteral nutrition (2.06; 1.27-3.33), >60 days of hospitalization (5.29; 4.02-6.95) and the neonatal unit where the neonate was born. The frequency of RBC transfusions varied among neonatal intensive care units. Even after adjusting for adverse health conditions and therapeutic interventions, the neonatal unit continued to influence transfusion practices in very-low birth-weight infants.
Keywords: Very low birth weight infants; Neonatal intensive care unit; Anemia; Red blood cell transfusion; Risk factors